Improvements in Schooling Opportunities and Teen Births - Lucas N. Garcez; María Padilla-Romo; Cecilia Peluffo; Mayra Pineda-Torres (Institute of Labor Economics (IZA), 2024)
We study the causal relationship between educational attainment and teenage birth rates by focusing on a large-scale, country-wide reform that made high school compulsory and removed previously existing school capacity constraints in Mexico. Relying on administrative data on schools and births, we implement a difference-in-differences strategy that exploits variation across time and municipality-level exposure to the reform to explore the effects of expanding educational opportunities on teenage fertility. We find that teenage birth rates decreased by 2.8 percent after the education reform in municipalities with high increases in high school availability relative to municipalities with low increases. This decline is not driven by a decline in the time teenagers had to engage in risky behaviors (incapacitation effect) but a potential change in expectations for the future.
Keywords: I12; I21; I28; J13; J16; 330; education reform; teenage birth rate; human capital